An integrated cellulose aerogel evaporator with improved thermal management and reduced enthalpy of evaporation using a hierarchical coordinated control strategy. Issue 12 (1st March 2023) - Sun, Jiaming; Teng, Rui; Tan, Jia; Xu, Mingcong; Ma, Chunhui; Li, Wei; Liu, Shouxin
Abstract : The synergistic effect between the water states, the evaporation sites and porous structure decreases the enthalpy of evaporation to 949 J g −1 and provides a single-module evaporator with a high evaporation rate of 3.17 kg h −1 m −2 . Abstract : Optimizing the structural design of solar-powered evaporators is an effective way to improve evaporation performance, but simplifying their design remains challenging. The balance between continuous water supply and thermal conductivity aggravated by hydrophilicity also needs to be solved. This work details an integrated cellulose aerogel based on a hierarchical coordinated control strategy. The Fe3 O4 -decorated photothermal conversion layer provides a solar radiation absorbance of 97%, while hollow hydrophobic glass bubbles (GBs) anchored in the insulation layer prevent the intrusion of water and provide the aerogel in wet state with a low thermal conductivity of 0.1008 W m −1 K −1 . A hydrophilic polyvinyl alcohol/cellulose skeleton ensures uninterrupted water transport while preventing salt accumulation. The synergistic effect obtained by increasing the depinning force at the contact line from GB-anchored heterogeneous vessel walls, adjusting the water states in the hydrophilic skeleton, and confining bulk water in a porous structure greatly reduces the enthalpy of evaporation to 949 J g −1 . The integration of all these functions provides a single-module evaporator with a high evaporation rate of 3.17 kg h −1 m −2 . The combination of improved thermal management, reduced enthalpy of vaporization and excellent salt resistance provides an effective water purification system with facile fabrication and low cost of maintenance.